Splenic Hemangiosarcoma in a 10- year male German Shepherd dog: Case Report - Ngetich W; Okumu AT; Kitaa JM; Chepkirui E (International Journal of Veterinary Science and Research - Peertechz Publications, 2017)
Hemangiosarcoma is a malignant tumor of endothelial cells and mostly seen in dogs than in other species. A 10-year male German shepherd dog (GSD) was presented to the small animal clinic with history of swollen abdomen and weakness. The dog was conscious but lethargic, weak, tachycardic with muffl ed heart sounds, labored breathing and tensed swollen abdomen. Radiography, Ultrasonography and a hemogram and biochemistry indicated splenic mass, internal hemorrhage and hemostasis pathology. The dog was euthanized and on post mortem examination, diagnosis of splenic  hemangiosarcoma was made. The current advances in screening tests for diagnosis and treatment options have increase the life span of affected animals.